Manufacturing the Image of a Country through Sport: Granma's Press Coverage of Cuba's Performance from the 1976 Montreal Olympics to the 2016 Rio Olympics. Issue 4 (4th March 2021) - Hasbani, Victor; Cortiñas-Rovira, Sergi; Ramon, Xavier
Abstract: Since Cuba's revolution in 1959, the country has found itself among the Olympic medal world leaders in terms of medals won against population size. Given the growing importance of the relationship between politics, major sporting events, and the media, this research uses predominantly qualitative methodology to analyze Cuban newspaper Granma 's coverage of the sporting successes of Cuba between the 1976 Montreal Olympics and the 2016 Rio Olympics. The longitudinal study of this 40-year period reveals that, in addition to its extensive coverage of the island's 'star' sports – baseball, boxing, athletics, and volleyball – the news publication has systematically and effectively used sporting achievements as a way of putting the country on the map and lending it political legitimacy, both locally and worldwide. The epic language that has dominated Granma 's narrative has served to extol the successes of government policies, making the country a guiding light for the whole of Latin America. Thanks to the constant presence of winning athletes, who have filled the pages with their highly politically charged and emotive declarations, the narrative adopted by the publication has also acted as the mouthpiece for the key values and ideas of the revolution.